Effects of surface modification and ultrasonic agitation on the properties of PHBV/ZnO nanocomposites - Bekat, Tugce; Oner, Mualla (WALTER DE GRUYTER GMBH, 2016)
Zinc oxide (ZnO) particles were synthesized from aqueous solution by chemical precipitation method. Self-aggregated rod-shaped particles were obtained. Silane modification and ultrasonic dispersion were compared in terms of effectiveness on particle deagglomeration. Complete deagglomeration was achieved with ultrasonic dispersion for untreated particles. Surface-treated and/or ultrasound-applied ZnO particles were incorporated into PHBV matrix by melt-extrusion. Good particle dispersion was achieved in the composites regardless of the agglomeration observed in particles prior to polymer matrix inclusion. Number of regular, rod-shaped particles observed was higher in the composites produced with ultrasound-dispersed particles. ZnO crystals did not affect the melting and crystallization temperatures of PHBV composites, but the degree of crystallinity was decreased. Thermal degradation temperature of PHBV was slightly decreased with ZnO addition. Tensile strength, elongation at break, and toughness of PHBV were affected positively when ultrasound-dispersed (treated or untreated) particles were incorporated into PHBV matrix; whereas application of both ultrasound and silane treatment produced better results.
Keywords: biocomposites; mechanical properties; PHBV; POC-16; silane; surface modification; thermal properties; ultrasonic dispersion; ZnO; BIODEGRADABLE POLYMERS; MECHANICAL-PROPERTIES; OXIDE; MORPHOLOGY; Chemistry